2018
DOI: 10.1681/asn.2017121334
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23 and Risks of Cardiovascular and Noncardiovascular Diseases: A Meta-Analysis

Abstract: Fibroblast growth factor-23 (FGF-23) has been hypothesized to play a role in the increased risk of cardiovascular disease in patients with CKD. We identified prospective studies reporting associations between FGF-23 concentration and risk of cardiovascular events. Maximally adjusted risk ratios (RRs) were extracted for each outcome and scaled to a comparison of the top versus bottom third of the baseline FGF-23 concentration, and the results aggregated. Depending on the assay used, median FGF-23 concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 77 publications
(137 reference statements)
3
126
3
1
Order By: Relevance
“…In accordance with Marthi et al [29], our data support the conclusion that elevated FGF23 increases the risk of all-cause mortality and CVD. In a word, FGF23 is a potential risk prediction factor and may be help for clinical practice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with Marthi et al [29], our data support the conclusion that elevated FGF23 increases the risk of all-cause mortality and CVD. In a word, FGF23 is a potential risk prediction factor and may be help for clinical practice.…”
Section: Discussionsupporting
confidence: 93%
“…Marthi et al [29] confirmed the association between FGF23 and mortality by meta-analysis. But Marcais et al [23] provided that evaluating the FGF23 without Klotho data may over highlight the detrimental effect.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Further, emerging data reveal that many stimuli outside of the mineral metabolism are able to increase FGF23 levels (inflammation, iron deficiency [63], high fat diet [64], as well as LV hypertrophy [65]). Lastly, a systematic review and meta-analysis of the prospective studies on the associations between FGF23 and the risk of different cardiovascular diseases suggests that the relationship between FGF23 and cardiovascular risk may be noncausal [66]. …”
Section: Future Directionsmentioning
confidence: 99%
“…Given that vascular smooth muscle cells in the presence of uremia and hyperphosphatemia are shown to transform into an osteoblastic phenotype, it is reasonable to hypothesize that reductions in phosphate and FGF23 coupled with enhanced clearance may in part contribute to the phenotypic changes in the arterial tree leading to a fall in systolic blood pressure . Whether FGF23 is a direct uremic cardiovascular toxin continues to be debated; in a recent meta‐analysis, some authors questioned the causal link between FGF23 and cardiovascular endpoints in chronic kidney disease . The present observation adds to the emerging evidence that FGF23 is modifiable by reduction in serum phosphorus .…”
Section: Discussionmentioning
confidence: 73%